Barriers and Opportunities in Circular Logistics: A Global Comparative Narrative Review - Widayat, Tri Agung; Mintje, Quirina Ariantji Patrisia; Yosepha, Sri Yanthy (Indonesian Scientific Publication, 2024)
This study reviews and synthesizes current knowledge on eco-efficient transport models within the frameworks of green logistics and the circular economy. The aim is to evaluate how technological, regulatory, and economic factors influence adoption and implementation. Literature was systematically gathered from major databases such as Scopus, Web of Science, and Google Scholar, using targeted keywords and Boolean search strategies. Inclusion criteria prioritized peer-reviewed articles published between 2018 and 2025 that addressed sustainable logistics, circular supply chains, and digital innovations. The review identified four major themes: drivers, barriers, case studies, and regional comparisons. Findings reveal that digital technologies, including artificial intelligence, blockchain, and the Internet of Things, enhance transparency, traceability, and efficiency. Regulatory frameworks, particularly in Europe, accelerate adoption, while economic incentives strengthen competitiveness. However, barriers persist, especially high initial costs, infrastructural deficits, and weak enforcement in developing economies. Case studies confirm measurable benefits, such as emission reductions and cost savings, while comparative analyses show significant regional disparities. The discussion emphasizes the importance of systemic alignment across policy, markets, and organizational culture to overcome these challenges. Future research is recommended to expand empirical evidence, develop standardized evaluation tools, and examine underrepresented regions. Overall, the review highlights the urgent need for integrated strategies that combine technology, regulation, and collaboration to advance sustainable logistics.